(untitled) (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Exploring the levels of knowledge and attitude of women towards alcohol use and related problems will enable a more efficient process of awareness creation and it will allow the program to be tailored more appropriately to the needs of the community. Females with alcohol problems are severely impaired; have adverse consequences and more alcohol related physical, psychological and social harm. Objective: To explore the knowledge and attitude of women towards alcohol use and related problems. Method: A hospital based cross sectional descriptive study. The selected participants were consecutive female patients with alcohol related problem who came under the health care service of psychiatry, consultation liaison and other departments of BPKIHS, Dharan scoring two or more scores in T-ACE questionnaire. The patients in abstinence for two or less than two months, more than 16 years of age and who gave informed written consent were included in the study. A semi- structured proforma was designed to collect the data.. Mean, Standard deviation and percentage was used for analysis. Results: A total of 49 female patients participated in the study after giving their written informed consent. The overall knowledge of the respondents regarding the alcohol use was inadequate as only 8 subjects (16.3%) had adequate knowledge (scored ≥ 60%). The mean score was 21.04±8.48 (43.8±17.6%). Positive attitude was shown by 64.46±21.93%. Negative attitude was shown by 25.76±16.76% and the rest 9.8% gave did not know response. Conclusion: The knowledge among the respondents was inadequate but the attitude towards alcohol use was positive. This indicates need for targeting an effective intervention.